Kekuatan Mengikat Klausula Arbitrase Dalam Kontrak Kerjasama Ditinjau Dari Hukum Perjanjian Dan Undang – Undang Nomor 30 Tahun 1999 Tentang Arbitrase - Bina Ariani, Taufiqoh; Amaliya, Lia; Syahrul Ansari, Teuku (Magister Kenotariatan, Universitas Jambi, 2024)
In order for the parties to be able to use arbitration as a means of resolving disputes that may or may not have already existed, the most important thing they need to do is come to an agreement in advance that is written down and approved by the parties. In view of this, the issues that will be examined in this paper are: What is the place of the assertion proviso in Regulation Number 30 of 1999 concerning Discretion and Elective Question Goal, How is the limiting force of the mediation condition in light of agreement regulation. The system utilized is regulating juridical and is concentrated on utilizing the resolution approach and is connected to the issues examined. This study's findings are based on Law No. 30 of 1999, which stipulates that parties must first enter into an arbitration agreement or clause before arbitrating a dispute can be resolved. The reason for the limiting force of the discretion statement is Article 1338 passage (1) of the Common Code and Article 11 of Regulation Number 30 of 1999. A contract has binding force and must be carried out by the parties if it contains an arbitration clause.